(untitled) (Orfeu, 2021)
The future is revealed as an increasingly nebulous and uncertain entity for contemporary society. Due to the rapid exchange of information, individuals are continually faced with an increasingly less hopeful scenario ahead of the next chapters of their life history. Several contemporary phenomena are in the genesis of hopelessness, in the limited look to the future, intrinsically changing the forms of social experience and present attitudes. In the search for that future, memory emerges as a phenomenon of continuous construction and reframing, and in its activity of building the perception of the past, also constructs the perception of the future. One of the greatest instruments that act on memory is musical activity, an action that shapes social and individual identities, one of the central phenomena in the construction of memory. It is proposed to question whether, from the musical activity, it is possible to broaden the horizon about the future.